THE ROLE OF HUMAN RESOURCE QUALITY AND PRODUCTION TECHNOLOGY ON THE OPERATIONAL COMPETITIVENESS OF MSMES IN TANGERANG REGENCY WITH MARKET ADAPTABILITY AS A MEDIATING VARIABLE - Nirfison; Abu Naim; Rahman Soesilo; Purwani Husodo; Ervina Yennie Permananingrum; Danu Noval Ramadhoni (RADJA PUBLIKA, 2025)
MSMEs in Tangerang’s Regency has a crucial role in boosting local economic growth, but it also has challenges in boosting operational competitiveness in a dynamic marketplace. This study aims to analyse the impact of Human Resource Management (HRM) quality and production technology on MSMEs operational day, using market flexibility as a mediating variable. This study employs a quantitative approach using the Structural Equation Modelling (SEM) method based on SmartPLS. File is gathered through questionnaires given to 200 MSMEs participants in the Tangerang province. The results of the data analysis indicate that SDM quality has a positive and significant impact on market adaptability (t-statistik = 6,134; p < 0,001) and operational daya saing (t-statistik = 5,221; p < 0,001). Additionally, production technology has a significant impact on market adaptability (t-statistik = 4,987; p < 0,001) and operational competitiveness (t-statistik = 4,653; p < 0,001). The market's ability to adapt significantly demonstrates the relationship between the two bebas variables and the day-to-day operations of MSMEs (t-statistik = 3,874; p < 0,001).This study highlights the importance of Human Resource development and adaptable production technology for the market in boosting MSMEs competitiveness in Tangerang province.